Systematic Literature Review : Application of Servant Leadership in Security and Aviation Services: Muhammad Aditya Ramadhan, Dhian Supardam - Ramadhan, Muhammad Aditya; Dhian, Supardam (Universitas Bojonegoro, 2024)
A systematic review of research articles on the application of servant leadership in the aviation industry highlights its significant positive impact on both service quality and workplace safety. Servant leadership, with its emphasis on employee well-being and development, has been shown to effectively improve safety behaviors and reduce accident risks, outperforming other leadership styles such as transactional and laissez-faire. This leadership model enhances employees' sense of ownership and responsibility, leading to greater job satisfaction, motivation, communication, and teamwork. Furthermore, servant leadership contributes to a more positive work environment, increasing employee loyalty, retention, and overall operational efficiency. Therefore, implementing servant leadership in the aviation sector not only reinforces a strong safety culture but also elevates the quality of services provided to customers.